The Relationship Between Serum YKL-40 Levels on Admission and Stroke-Associated Pneumonia in Patients with Acute Ischemic Stroke - Shi G (Dove Medical Press, 2021)
Guomei Shi,1,2,* Wenxiu Chen,3,* Pengyu Gong,4 Meng Wang,4 Junshan Zhou,4 Xiaorong Wang,1 Minwang Guo,1 Jingye Lu,1 Yan Li,1 Hongxuan Feng,2,5 Xuetao Fu,2,6 Rujuan Zhou,1 Shouru Xue2 1Department of Neurology, The Taixing People’s Hospital, Taixing, Jiangsu, People’s Republic of China; 2Department of Neurology, The First Affiliated Hospital of Soochow University, Suzhou, Jiangsu, People’s Republic of China; 3Department of Critical Care Medicine, Nanjing First Hospital, Nanjing Medical University, Nanjing, Jiangsu, People’s Republic of China; 4Department of Neurology, Nanjing First Hospital, Nanjing Medical University, Nanjing, Jiangsu, People’s Republic of China; 5Department of Neurology, The Affiliated Suzhou Hospital of Nanjing Medical University (Suzhou Municipal Hospital), Suzhou, Jiangsu, People’s Republic of China; 6Department of Neurology, Affiliated Hospital of Yangzhou University, Yangzhou, Jiangsu, People’s Republic of China*These authors contributed equally to this workCorrespondence: Rujuan Zhou; Shouru Xue Tel +86-13951158499; +86-18962133036Email zhourujuan123@163.com; xueshouru@suda.edu.cnBackground: Stroke-associated pneumonia (SAP) is a standout complication after acute ischemic stroke (AIS), with a prevalence of 7– 38%. The aim of this prospective study was to investigate the relationship between serum YKL-40 levels at admission and SAP.Methods: Between August 2020 and February 2021, consecutive AIS patients from two centers were enrolled prospectively. Serum YKL-40 concentrations were measured via enzyme-linked immunosorbent assay. We performed logistic regression analyses to explore the relationship between YKL-40 and SAP. Receiver operating characteristic curve was also used to assess the predictive ability of YKL-40 in predicting SAP.Results: Ultimately, a total of 511 AIS patients were recruited. Multivariate logistic regression analysis showed that YKL-40 was independently related to SAP, whether as a continuous variable or as quartiles (P=0.001). The area under curve of YKL-40 to predict SAP was 0.765. The optimal cutoff value of YKL-40 as a predictor of SAP was determined to be 206.4 ng/mL, where the sensitivity was 63.1% and the specificity was 82.0%.Conclusion: Our study demonstrated that YKL-40 might be considered as a useful biomarker to predict SAP in AIS patients.Keywords: acute ischemic stroke, YKL-40, stroke-associated pneumonia